Comparison of Acoustocerebrography Measurement and Magnetic Resonance Imaging Methods in the Assessment of White Matter Lesions in Patients with Atrial Fibrillation - DOBKOWSKA-CHUDON, Wioletta; WROBEL, Mirosław; FRANKOWSKA, Emilia; ZEGADLO, Arkadiusz; KRUPIENICZ, Andrzej; NOWICKI, Andrzej; OLSZEWSKI, Robert (Archives of Acoustics, 2020)
The brain is subject to damage, due to ageing, physiological processes and/or disease. Some of the damage is acute in nature, such as strokes; some is more subtle, like white matter lesions. White matter lesions or hyperintensities (WMH) can be one of the first signs of micro brain damage. We implemented the Acoustocerebrography (ACG) as an easy to use method designed to capture differing states of human brain tissue and the respective changes. Aim: The purpose of the study is to compare the efficacy of ACG and Magnetic Resonance Imaging (MRI) to detect WMH in patients with clinically silent atrial fibrillation (AF). Methods and results: The study included 97 patients (age 66.26 ± 6.54 years) with AF. CHA2DS2-VASc score (2.5 ±1.3) and HAS BLED (1.65 ± 0.9). According to MRI data, the patients were assigned into four groups depending on the number of lesions: L0 – 0 to 4 lesions, L5 – 5 to 9 lesions, L10 – 10 to 29 lesions, and L30 – 30 or more lesions. Authors found that the ACG method clearly differentiates the groups L0 (with 0–4 lesions) and L30 (with more than 30 lesions) of WMH patients. Fisher’s Exact Test shows that this correlation is highly significant (p < 0:001). Conclusion: ACG is a new, easy and cost-effective method for detecting WMH in patients with atrial fibrillation.